Densely homogeneous fuzzy spaces - Samer Al Ghour (Institute of Advanced Engineering and Science, 2019)
We extend the concept of being densely homogeneous to include fuzzy topological spaces. We prove that our extension is a good extension in the sense of Lowen. We prove that a-cut topological space (X,I_a) of a DH fuzzy topological space (X,I) is DH in general only for a=0.